Sarcopenia and ovarian cancer survival: a systematic review and meta‐analysis. Issue 6 (7th August 2019) - Ubachs, Jorne; Ziemons, Janine; Minis‐Rutten, Iris J.G.; Kruitwagen, Roy F.P.M.; Kleijnen, Jos; Lambrechts, Sandrina; Olde Damink, Steven W.M.; Rensen, Sander S.; Van Gorp, Toon
Abstract: Background: Sarcopenia is the loss of skeletal muscle mass and function that occurs with advancing age and certain diseases. It is thought to have a negative impact on survival in cancer patients. Routine computed tomography imaging is often used to quantify skeletal muscle in cancer patients. Sarcopenia is defined by a low skeletal muscle index (SMI). Skeletal muscle radiation attenuation (SMRA) is used to define muscle quality. The primary aim of this meta‐analysis was to study the association between sarcopenia or SMRA and overall survival (OS) or complications in patients with ovarian cancer. Methods: Medline, Embase, CINAHL, and PEDro databases were searched from inception to 15 February 2019. Studies evaluating the prognostic effect of SMI and SMRA on ovarian cancer survival or surgical complications were included. Risk of bias and study quality were evaluated with the Quality in Prognosis Studies Instrument (QUIPS) according to the modified Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework. Results: The search strategy yielded 4262 hits in all four databases combined. Ten and eight studies were included for qualitative and quantitative analysis, respectively. Meta‐analysis revealed a significant association between the SMI and OS [0.007; hazard ratio (HR): 1.11, 95% confidence interval (CI): 1.03–1.20]. SMRA was also significantly associated with OS ( P < 0.001; HR: 1.14, 95% CI: 1.08–1.20). Association between the SMI and surgical complications had borderline statistical significance (0.05; HR: 1.23, 95% CI: 1.00–1.52). The risk of bias assessed with QUIPS was high in all studies. The quality of the evidence was very low. Conclusions: Whereas our meta‐analysis indicated that a low SMI and low SMRA are associated with survival in ovarian cancer patients, the low quality of the source data precludes drawing definitive conclusions.